Über die Natur und das Wesen des Geldes: Johann Heinrich von Thünens unveröffentlichter Beitrag zur Geldtheorie - Ludwig Nellinger (Universität Rostock, Institut für Volkswirtschaftslehre, 2009)
The economic works of Johann Heinrich von Thünen include 1,000 unpublished pages of drafts and notes on the basis of which he prepared the second volume of his famous 'Isolated State in Relation to Agriculture and Political Economy'. Thünen wrote his texts in the so-called Deutsche Kanzleischrift, a script which can be read today only by specialised historians, rarely by economists. In a first part of a research project of the Thünen-Gesellschaft e.V. 300 pages were transliterated, from which the first 60 pages were reviewed until October 2009. It becomes obvious that Thünen's work is much more far-reaching than the contributions published by himself or edited by Schumacher in 1863 and 1875 show. Its bulk was not made accessible until today. This can be easily demonstrated by the content of these first 60 pages, especially those treating monetary questions and preparing Thünen's theory of capital and interest. Thünen starts his analysis with a description of the diminishing return of money keeping in an enterprise. He considers both the exchange and the stock function of money. He describes the pros and cons of the creation of paper money as a substitute for coins. Thünen is the first economist who develops an extended quantity theory of money by introducing the velocity of money transactions and formulating the correct algebraic formula. He anticipates the famous Newcomb-Fisher equation but with one difference: in Thünen's opinion the product of velocity and quantity of money primarily determines the value of circulating capital goods and assets, an argument which has to be understood with the contemporary rural economic conditions in mind. He analyses the liquidity effect of positive exogenous money shocks. By describing the adaptation processes in the case of differences between the monetary market interest rate and the real rate of return on capital goods, Thünen presents important mechanisms of Knut Wicksell's 'Interest and Prices', which were published 75 years later and still inspire the monetary economists today. In accordance with Henry Thornton, he adequately describes the consequences of liquidity preference in the case of uncertain economic situations. In our opinion Thünen's 1823 contribution is of the same quality as the contributions of the leading monetary theorists in the early 19th century, David Ricardo and Henry Thornton. With respect to the further theoretic development in the nineteenth and twentieth century and from the perspective of modern monetary theory, Thünen's drafts are an unexpected discovery and of particular interest in the current financial and economic crisis. The paper concludes with a preliminary assessment of Thünen's text in the context of the sec-ond volume of the 'Isolated State', which was published in 1850 and which contains Thünen's 'Theory of Capital and Interest'.
Keywords: B13; B16; D53; E31; G12; 330; Dogmengeschichte; Kapital- und Zinstheorie; Quantitätstheorie; Verkehrsgleichung; Geldnachfrage; Liquiditätspräferenz; Geldtheorie; Dogmengeschichte; Theorie